Novel role analysis method for network domain users - Xiao-feng XU; Li YANG; Wei WANG (网络与信息安全学报)
A novel role analysis method for network domain users was proposed.Firstly,the algorithm used ISODATA algorithm to cluster network events for user behavior analysis,on the basis of conditions,the method search relationships between varieties of grouping sets in the network instance,and identify each user role in the performing process of network instance.Finally,simulation results show that the effectiveness of the proposed algorithm can distinguish the network user hierarchy and obtain the dominant roles about network users.